Development of the investment services market in a competitive environment ("Journal "U". Economy. Management. Finance.", 2025)
The article discusses current issues of the development of the investment services market in modern competitive conditions. The relevance of the research is due to the increasing role of investment services in the economic development of the country and the need to improve the efficiency of this market in the face of increasing competition. The paper provides a comprehensive analysis of the current state of the investment services market, identifies the main trends in its development and factors affecting the competitive environment. Special attention is paid to the research of innovative approaches to the provision of investment services and the digital transformation of the market. Based on the conducted research, practical recommendations are proposed for improving the mechanisms of functioning of the investment services market and increasing its competitiveness. The results obtained can be used in developing strategies for the development of investment companies and improving government regulation of this area.
Keywords: investment services; competition; market mechanisms; digitalization; financial market; investment companies; competitiveness; innovative development; investment products; financial technologies